Pembelajaran Membaca Al-Qur’an dengan Menggunakan Metode Tajdied pada Siswa Sekolah Dasar - Kulzum, Putri Maja Mulia (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) STIB Banyuwangi, 2021)
Al-Qur'an is the holy book that was given to us Muslims as a gift. Allah provides many conveniences for those who want to learn it. Both in terms of reading, memorizing, interpretation and various other scientific fields. For this reason, there is no more important knowledge for a Muslim to learn than the virtue of studying the Al-Quran and knowing how to apply the reading of the al-7 with the tajdied method to elementary school students as well as the factors that support, hinder learning Al-quran. This research uses qualitative research, the research intends to understand what is experienced by research subjects in a special context. In this study, data collection using observation, interviews, and documentation. Furthermore, data processing uses three main steps in research, namely: data reduction, data presentation (data display), data verification (summarizing data). In the results of this study, there is a planning for learning to read the Al-qur'an with the tajdied method, including curriculum and media through this method which can provide responsiveness in reading the Koran for elementary school students, in practice the teacher carries out teaching and learning interaction activities guided by on the teaching preparation that has been made. Teaching materials are given according to the order that has been programmed systematically in the preparation stage and the teacher still pays attention to the principles of teaching. The evaluation of learning to read the Koran using the tajdied method is whether the students are successful in reading the Koran, including the components of tajwid and makhorijul letters.